New approach to pathogenesis and treatment of trophycal ulcers - Arzu M. Musayeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Introduction. Trophic ulcers are one of the most common medical ailments worldwide. Treatment of patients with trophic ulcers is difficult not only because they often recur, but also because they are difficult to treat. Purpose. Study the clinical features and present our own results of combined methods of treatment of trophic ulcers of venous etiology. Materials and methods. The study involved 100 patients with trophic ulcers of the lower extremities of venous, diabetic and atherosclerotic etiology, who had a history and were treated for varicose veins of the lower extremities and post-thrombotic disease. Examination of patients included questionnaires, clarification of complaints, anamnesis data, causes of development, examination and ultrasound diagnostics (duplex examination). The examination of the ulcer included determining the location, size, appearance, base of the wound, the level of exudation and assessment of the condition of the skin around the defect. Results. The etiological factors in the development of trophic ulcers were: varicose disease with chronic venous insufficiency – 25 patients, post-thrombotic disease – 55 patients. All patients underwent only conservative treatment of trophic venous ulcers with the appointment of a placenta compositum. After the treatment of a group of patients, out of 100 patients with venous trophic ulcers, 89% were cured within 4 months, 8% were cured within 2 years, and in 3 % ulcers did not heal for more than two years. The average duration of the course of ulcers was 12 months. The average size of trophic ulcers based on the results of the analysis was 8 cm2. Complete healing of venous ulcers was most often observed in the age group 61–73 years in 30% patients. Conclusion. The use of the compositum placenta contributed to the acceleration of wound healing, which made it possible to obtain more effective results.